Research progress on serological and clinical diagnostic assays of porcine epidemic diarrhea virus - LEI Ximei; YANG Yongle; XU Shuya; ZHAO Pengwei; WANG Bin; HUANG Yaowei (浙江大学学报. 农业与生命科学版)
Porcine epidemic diarrhea virus (PEDV) is a causative agent of acute, highly contagious porcine epidemic diarrhea (PED). It infects pigs of all ages and results in high mortality rates particularly in suckling piglets. Current vaccines can not provide efficient protection to infected piglets. Thus, developing safer and more efficacious vaccines is fundamental to the control of PEDV. Meanwhile, it is of significance in establishing sensitive and efficient serological assays for clinical diagnosis of PEDV infection as well as the surveillance and evaluation of humoral responses at post-vaccination. In this review, we summarized the current serological assays and discussed the antibody kinetics at post-infection or vaccination, aiming to provide references to the diagnoses and control of PEDV.